“USING AUDIO-VISUAL AND INTERACTIVE METHODS TO ENHANCE PHYSICAL SKILLS IN VISUALLY IMPAIRED STUDENTS” - Qurbonova Nasiba Mirsalim qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article investigates the effectiveness of audio-visual and interactive methods in developing physical skills in visually impaired students. The study emphasizes preparatory classes where exercises are adapted to individual needs and incorporate sensory feedback to improve endurance, balance, coordination, and agility. The research highlights safety, individualized instruction, and the motivational benefits of multi-sensory learning.